1992
DOI: 10.1159/000182572
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function during Growth Hormone Therapy

Abstract: Administration of growth hormone (GH) in GH-deficient patients has been reported to cause a variety of perturbations in thyroid function. Reports range from decreased sensitivity of thyrotropin (TSH) to thyrotropin-releasing hormone (TRH) stimulation and induction of hypothyroidism to increased energy expenditure and enhanced peripheral thyroxine (T4) to triiodothyronine (T3) conversion. Some of the diversities may relate to the fact that earlier studies were uncontrolled case reports, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 14 publications
(14 reference statements)
5
16
2
Order By: Relevance
“…To our knowledge, the observed baseline T 3 abnormalities in 20% of GHD PWS subjects and their normalization with GH therapy are unique. However, they are consistent with reports in children with PWS (30) and in non-PWS GHD adults, documenting dose-dependent enhancement of extrathyroidal T 4 to T 3 conversion (13)(14)(15)31) and suppression of circadian TSH levels after the administration of GH (15,32) as well as with other widely reported subtle, but notable complexities in the interaction of GH with the hypothalamic-pituitary-thyroid axis (32). The concomitant group mean reduction in total T 4 levels after GH (8.6 to 7.9 ng/dl, P ϭ 0.05) provides additional evidence of increased deiodination of T 4 in our PWS subjects and supports the hypothesis that peripheral conversion of T 4 to T 3 may contribute to GH-mediated enhancement of resting energy expenditure and LBM (15).…”
Section: The Thyroid Axis In Pwssupporting
confidence: 91%
“…To our knowledge, the observed baseline T 3 abnormalities in 20% of GHD PWS subjects and their normalization with GH therapy are unique. However, they are consistent with reports in children with PWS (30) and in non-PWS GHD adults, documenting dose-dependent enhancement of extrathyroidal T 4 to T 3 conversion (13)(14)(15)31) and suppression of circadian TSH levels after the administration of GH (15,32) as well as with other widely reported subtle, but notable complexities in the interaction of GH with the hypothalamic-pituitary-thyroid axis (32). The concomitant group mean reduction in total T 4 levels after GH (8.6 to 7.9 ng/dl, P ϭ 0.05) provides additional evidence of increased deiodination of T 4 in our PWS subjects and supports the hypothesis that peripheral conversion of T 4 to T 3 may contribute to GH-mediated enhancement of resting energy expenditure and LBM (15).…”
Section: The Thyroid Axis In Pwssupporting
confidence: 91%
“…In our patients, a significant increase in fT 3 at 12 months of therapy is documented in the majority of cases, in line with the data of Seminara et al [16], without a significant relationship with IGF-1 and without any impact on catch-up growth. These changes, independently of TSH levels, might be an expression of the metabolic status of patients at that moment and could be explained by an increased GH-induced T 4 to T 3 deiodination, as previously reported [12,14,36]. The evidence that GHD reduces T 4 to T 3 conversion and GH improves T 4 to T 3 conversion through iodothyronine deiodinase activity is well known in animal models [37,38,39].…”
Section: Discussionsupporting
confidence: 52%
“…Thyroid hormone replacement in the hypopituitary patient cannot be titrated against serum TSH, the most sensitive index of tissue activity of thyroid hormones, and thus subtle degrees of overand underreplacement with thyroid hormones likely occur in hypopituitarism. GH, through increased 5Ј-deiodinase activity, increases conversion of T 4 to metabolically active T 3 (7), and it has been suggested that this effect might underlie some of the metabolic changes observed with GH replacement (107,108). Untreated testosterone deficiency in males is associated with reduced LBM, increased body fat, and reduced exercise capac- ity, whereas orally administered estrogen reduces fat oxidation and increases body fat in normal women (109,110).…”
Section: Limitations Of Using Ghd Adults To Study the Physiologicamentioning
confidence: 99%